ПРОГРАМНО-АЛГОРИТМІЧНЕ ЗАБЕЗПЕЧЕННЯ ОПТИКО-ЕЛЕКТРОННИХ ВИМІРЮВАЧІВ КОМП’ЮТЕРИЗОВАНИХ СИСТЕМ КОНТРОЛЮ ТА ДІАГНОСТИКИ МЕХАНІЧНИХ ДЕФЕКТІВ ПОТУЖНИХ ГЕНЕРАТОРІВ - Зайцев, Є.О. (Інститут електродинаміки Національної академії наук України, 2020)
The main goal of this paper it's considered the special software algorithms creation for the opto-electronic transducers for powerful generators mechanical fault diagnosing systems. For analysis of what functions are needed in the algorithms, the physical processes with influencing on mechanical defects evolution in powerful generators are presented. The necessity of solving important scientific and practical problem detection and identification of defects to ensure the safety, reliability, and durability of large generators is shown. The solution to the problem requires the implementation of software and algorithmic support for electron-optical meters included in the control systems and technical diagnostics of powerful generators. The advantages and disadvantages of secondary measuring transducers, which can be used to implement electron-optical meters of mechanical defects studied. The possibility of using as a converter capacitance-to-digital converter integrated circuit AD7745/46. A block diagram of the hardware and software of an optical-electronic meter with a secondary measuring transducer based on the AD7745/46 integrated circuit in the structure of the hardware and software of a computerized control system and technical diagnostics of powerful generators is presented. A general algorithm has been developed for the functioning of a secondary meter of mechanical defects of powerful generators based on the AD7745/46 integrated circuit. References 20, fig. 3.